Principles of Smile Analysis in Orthodontics- A Clinical Overview - Singh, Varun Pratap; Sharma, JN (Health Renaissance, 2011)
"It all begins with a smile" is a proverb which, highlights the importance of smile in social outlook and quality of life. With the face first paradigm, orthodontics has put more emphasis on the dental and facial appearance as it has a direct psychosocial impact. Modern orthodontics deals with not only the traditional dental and skeletal aspects but soft tissue drape or face as first priorty.Orthodontic treatment planning must incorporate various principles of smile analysis to achieve desirable results. This article describes principles of smile analysis that should be considered during orthodontic treatment planning and various attributes of a pleasing smile. Keywords: smile analysis; esthetic paradigm; smile arc DOI: 10.3126/hren.v9i1.4360 Health Renaissance, 2011: Vol.9 No.1:35-40